Diversity of Leptoceroidea (Insecta: Trichoptera) in Pará State, Brazil: A new species of Oecetis McLachlan 1877 and new records - Moura, Laisse; Quinteiro, Fábio B. (Zootaxa, 2023)
The order Trichoptera contains approximately 17,250 described species and their individuals are important freshwater environment components, frequently used as bioindicators of environmental quality. Despite recent advances in the knowledge of caddisflies in the Neotropical region, there are gaps to be filled, especially in critically endangered biomes, such as the Amazon rainforest, which has its largest area in the North Region of Brazil. In this region of Brazil, the state of Pará presents a promising scenario for biodiversity studies, since a great portion of its area is covered by the Amazon rainforest and distinct environments (e.g., mangroves and rainforest). Knowledge about Trichoptera in the state includes 97 species records, 12 of them belonging to Leptoceroidea. To improve knowledge regarding the Amazon fauna, we record nine species of Leptoceroidea for the first time in Pará State: Marilia alata, Nectopsyche muhni, Nectopsyche multilineata, Oecetis bidigitata, Oecetis cassicoleata, Oecetis doesburgi, Oecetis iguazu, Phylloicus auratus, and Triplectides maranhensis; we also describe and illustrate one new species: Oecetis ancorospina n. sp. which belongs to the Oecetis testacea Species Group.